The gut microbiome modulates response to cancer immunotherapy - Khan, Md. Abdul Wadud (Dig Dis Sci, 2020)
With the advent of next generation sequencing approaches, there has been a renaissance in the microbiome field. Microbial taxonomy and function can now be characterized relatively easily and rapidly - no longer mandating complex culturing approaches. With this renaissance, there is now a strong and growing appreciation for the role of the microbiome (referring to microbes and their genomes) in modulating many facets of physiology - including overall immunity. This is particularly true of the gut microbiome, and there is now an evolving body of literature demonstrating a role for gut microbes in modulating responses to cancer treatment - particularly immunotherapy. Gut microbes can modulate immunity and anti-tumor responses via a number of different interactions, and these will be discussed herein. Additionally, data regarding the impact of gut microbes on cancer immunotherapy response will be discussed, as will strategies to manipulate the microbiome to enhance therapeutic responses. These efforts to date are not completely optimized, however there is evidence of efficacy though much additional work is needed in this space. Nonetheless it is clear that the microbiome plays a central role in health and disease, and strategies to manipulate it in cancer and overall precision health are being explored.